Utilization of Safe Motherhood Services in a Tertiary Referral Hospital in Western Region of Nepal - Choudhary, Rajendra Kumar; Jha, N.K.; Manandhar, B. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: It has been two decades Nepal has initiated safe motherhood programme in 1998, since then there has been significant reduction in maternal mortality and improvement in newborn care. Western Regional Hospital is the government referral hospital in western Nepal and has large volume of patients utilizing the safe motherhood services. This study is a review of one year of different safe motherhood services provided by this hospital.Methods: The data from the hospital records section from Asoj 2073 (September - October 2016) to Bhadra 2074 (August - September 2017)has been extracted from the hospital record section and analyzed in terms to different services like antenatal visits, vaginal delivery, caesarean section, incomplete abortion and ectopic pregnancy. The obtained data was entered and analyzed using Microsoft Excel.Results: Total of 42,798 patients had utilized the safe motherhood services during the study periods, majority of them being antenatal visits followed by vaginal and caesarean delivery. Some of the vaginal deliveries 490 (5.3%) were complicated which included vacuum delivery, intrauterine fetal death, twins and breech delivery. Among the total delivery 2316(24.8%) were caesarean sections, of which more than halves were due to emergency indications.Conclusions: The safe motherhood program in Western Regional Hospital has positive impact on the maternal health in this region and further expansion of the services and facilities are recommended in coming days in scenario of increasing number of patients.